2009
DOI: 10.1007/s00268-009-0074-7
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Pooled Estimates for the Diagnostic Accuracy of Serological Markers for Intestinal Ischemia

Abstract: The performance of the currently available serological markers is suboptimal for routine clinical use, but novel markers of intestinal ischemia such as D-lactate, GST, and i-FABP may offer improved diagnostic accuracy. The early diagnosis of intestinal ischemia remains a challenge, and further research is required to identify improved serological markers and to demonstrate their clinical utility in the individual patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
180
2
20

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(209 citation statements)
references
References 63 publications
7
180
2
20
Order By: Relevance
“…Poeze et al 32 found that serum D-lactate is consistently increased in intestinal ischemia, with sensitivity and specificity of 82 and 72% respectively. Evennett et al 33 have also added to this point of view.…”
Section: Discussionmentioning
confidence: 99%
“…Poeze et al 32 found that serum D-lactate is consistently increased in intestinal ischemia, with sensitivity and specificity of 82 and 72% respectively. Evennett et al 33 have also added to this point of view.…”
Section: Discussionmentioning
confidence: 99%
“…[2,11] In an earlier study [25] of RDW in the context of diagnosing AMI, cut-off value, sensitivity, and specificity were 15.04%, 40.8%, and 81.2%, respectively. Another study [26] found that the AUC for RDW was 0.713, and that the cut-off value was 14.85%.…”
Section: Discussionmentioning
confidence: 99%
“…During this process, inflammatory substances measurable in peripheral blood are released from necrotic cells of the gut wall. [2,6] Recent studies have focused on such materials because early and accurate detection of inflammation is essential in order to optimize treatment and prognosis of those with medical emergencies. [7] Several biomarkers, such as C-reactive protein (CRP), procalcitonin, and mean platelet volume (MPV) have been used as indicators of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…While many blood analyses, such as lactate dehydrogenase, transaminases, D-dimer, D-lactate, and creatinine phosphokinase have been suggested for diagnosis of AMI, as yet, none is sufficiently specific or sensitive. [3] Diagnosis can usually be made based The aim of the present study was to investigate the predictive value of MPI together with P/L ratio, a hematological marker, with respect to prognosis in patients with AMI.…”
Section: Introductionmentioning
confidence: 99%